Dreams of nationhood : American Jewish communists and the Soviet Birobidzhan project, 1924-1951 - Srebrnik, Henry Felix (Jewish identities in post modern society., 2010)
The American Jewish Communist movement played a major role in the politics of Jewish communities in cities such as Boston, Chicago, Los Angeles, New York, and Philadelphia, as well as in many other centers, between the 1920s and the 1950s. Making extensive use of Yiddish-language books, newspapers, periodicals, pamphlets, and other materials, Dreams of Nationhood traces the ideological and material support provided to the Jewish Autonomous Region of Birobidzhan, located in the far east of the Soviet Union, by two American Jewish Communist-led organizations, the ICOR and the American Birobidzhan Committee. By providing a detailed historical examination of the political work of these two groups, the book makes a substantial contribution to our understanding of twentieth century Jewish life in the United States.